Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system. (20th March 2023) - Cheng, Hao; Li, Xinyan; Huang, Chao; Zhu, Jian; Wang, Ping; Cao, Heng; Feng, Chongling; Ling, Dingxun; Liu, Hao; Cheng, Min
Abstract: Commercial molybdenum carbide (Mo2 C) and ferrous iron (Fe 2+ ) were investigated for the first time to co-catalyze the activation of H2 O2 for the treatment of organic contaminants. Compared with traditional Fenton process, the presence of Mo2 C decomposed hydrogen peroxide (H2 O2 ) more effectively and accelerated the conversion of Fe 3+ /Fe 2+ . The Rhodamine B (RhB) degradation rate constant in Mo2 C/Fe 2+ /H2 O2 reached appropriately three times that in Fe 2+ /H2 O2, and the co-catalytic reactivity of Mo2 C was significantly higher than that of MoS2 . In addition, Mo2 C/Fe 2+ /H2 O2 exhibited a board effective pH range of 2.8–8.8, and four-cycle experiments confirmed the stability and reusability of Mo2 C. The results of X-ray photoelectron spectroscopy (XPS) indicated that Mo(Ⅱ) and Mo(IV) played major roles in Fe 3+ reduction. Electron Paramagnetic Resonance analysis and quenching experiments demonstrated that hydroxyl radical (·OH), superoxide anion radical (O2 − ) and singlet oxygen radical ( 1 O2 ) were all involved in Mo2 C/Fe 2+ /H2 O2 . Particularly, Mo2 C/Fe 2+ /H2 O2 significantly enhanced the generation of ·OH and 1 O2 in comparison to Fe 2+ /H2 O2 . Moreover, toxicity assessment analysis by ECOSAR suggested that the toxicity of most degradation products of RhB decreased after treatment. Overall, this study offers a promising Mo2 C co-catalyzed Fenton process for rapid and efficient abatement of organic contaminants. Graphical abstract: Image 1 Highlights: A novel Mo2 C based Fenton-like process with a wide effective pH range was developed. The K obs and H2 O2 utilization efficiency were 0.6405 min −1 and 90.2%, respectively. Mo2 C/Fe 2+ /H2 O2 showed a higher K obs and H2 O2 utilization efficiency than Fe 2+ /H2 O2 . Radicals (·OH and ·O2 − ) and non-radical ( 1 O2 ) were involved in the reaction. Toxicity assessment revealed a low ecotoxicity of most degradation intermediates.